(untitled) (City: History, Culture, Society, 2025)
Berdiansk is a Ukrainian city on the Azov Sea shore in Zaporizhzhia Oblast. With almost 200 years of colonial history, this city currently living under Russian occupation is an excellent fit for analysing the memory transformation process in the communities of southeastern Ukraine. This paper examines the memory politics background in the southeast of Ukraine as exemplified by the changes in symbolism across Berdiansk’s city space on the back of post-Maidan politics. In addition, it describes and discusses the transformation of memory sites under occupation and imagines potential commemoration frameworks for the liberated Berdiansk. The considerations for symbolical transformations in Berdiansk draw on the Content Analysis method. Some data comes from the interview with the Research Institute of Urban History Director, Prof. Victoria Konstantinova, who helped implement decommunisation laws. While analysing the relations between Ukrainian memory politics and Russian colonial policy, the author used de/postcolonial optics.